Odpowiedzi

Najlepsza Odpowiedź!
2009-12-08T15:17:56+01:00
A)3m+n=9
2m-5n=-11

n=9-3m
2m-5*(9-3m)=-11

n=9-3m
2m-45+15m=-11

n=9-3m
17m=34 /:17

n=9-3m
m=2

n=9-3*2
m=2

n=3
m=2

b.)4a-2=b
3a+7b=1,5

b=4a-2
3a+7(4a-2)=1,5

b=4a-2
3a+28a-14=1,5

b=4a-2
31a=15,5 /:31

b=4a-2
a=0,5

b=4*0,5-2
a=0,5

b=0
a=0,5
2009-12-08T15:19:53+01:00
A)
3m + n = 9
2m - 5n = -11

n=9-3m
2m -5*(9-3m) =-11

n=9-3m
2m -45 +15m=-11

n=9-3m
17m=-11+45

n=9-3m
17m=34 /:17

n=9-3m
m=2

n=9-3*2
m=2

n=9-6
m=2

n=3
m=2

b)
4a - 2 = b
3a + 7b = 1,5

b=4a-2
3a+7(4a-2)=1,5

b=4a-2
3a+28a-14=1,5

b=4a-2
31a=1,5+14

b=4a-2
31a=15,5 /:31

b=4a-2
a=0,5

b=4*0,5-2
a=0,5

b=2-2
a=0,5

b=0
a=0,5

2009-12-08T15:20:57+01:00
A)
3m+n=9 / *2
2m-5n=-11/ *-3

6m+2n=18
-6m+15n=33
--------------------
17n=51
n= 3

3m+n=9
3m+3=9
3m=9-3 n=3
3m=6 m=2
m=2

b)
4a - 2 = b
3a + 7b = 1,5

4a-b=2 / *7
3a+7b=1,5

28a-7b=14
3a+7b=1,5
-----------------------
31a=15,5
a=0,5


4a-2=b
4* 0,5 -2=b a=0,5
2-2=b b=0
b=0


PROSZĘ BARDZO ;)